MicroRNA regulator gene mutations in thyroid follicular nodular disease and thyroid cancer: does it all come down to timing? - Vincenzo Condello; C Christofer Juhlin (European Thyroid Journal, 2024)
In recent years, germline mutations in the microRNA (miRNA) processor genes DICER1 and DGCR8 have been coupled to the development of thyroid follicular nodular disease (TFND), thereby casting new light on the etiology of this enigmatic, benign condition in non-iodine-deficient regions. Moreover, DICER1 and DGCR8 mutations have also been reported in rare subsets of follicular cell-derived thyroid carcinomas. Specifically, truncating germline or missense somatic DICER1 mutations have been reported in small subsets of pediatric and adolescent follicular thyroid carcinoma (FTC) and poorly differentiated thyroid carcinoma (PDTC). Similarly, a recurrent somatic mutation of the DGCR8 gene has been observed in highly aggressive FTCs and in some indolent cases of encapsulated follicular variant of papillary thyroid carcinoma. The reason why identical mutations in the same miRNA processor gene can lead to such a myriad of thyroid conditions, ranging from benign TFND to FTCs and PDTCs, remains unclear. This review highlights key features of miRNA regulator gene mutations in thyroid disease and explores their potential roles as drivers or progression events in tumor development.